Alleviation Strategies Of Stunting In Infants' Problems Using Tilapia Fish Farming In Sukodono District, Lumajang Regency - Kilawati, Yuni; Putri, Ardyah R.I.; Fahma, Yunita Rifda Alano; Dara, Yuliezar Perwira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Various programs to fulfill community nutrition by the government in Sukodono District have been actively implemented to alleviate the problem of stunting. Our service activities are based on strategic issues faced in Sukodono District, consisting of education regarding the causes and solutions to the stunting problem and socializing one of the efforts to eradicate stunting. Supported by the Lumajang Regency Government, it has made various efforts to handle and alleviate stunting in Lumajang, so this outreach activity provides insight to the community, especially posyandu cadres, prospective brides, and mothers. This activity aims to help the communities in the Sukodono District, Lumajang Regency, to eradicate the problem of stunting by socializing the tilapia fish farming model and the benefits of tilapia fish. The activity is community service through socialization, which can increase public understanding before and after presenting material on tilapia program activities to prevent stunting.